Phylogenomic Analysis of Nassula variabilis n. sp., Furgasonia blochmanni, and Pseudomicrothorax dubius Confirms a Nassophorean Clade - Lynn, Denis H; Kolisko, Martin; Bourland, William (Protist, 2018)
The class Nassophorea includes the microthoracids and nassulids, which share morphological similarities in their somatic kinetids and cytopharyngeal baskets. The monophyly of this clade has been challenged by small subunit rRNA gene sequences and multi-gene analyses that do not provide strong support. To provide a more robust test of the monophyly of the Nassophorea, phylogenomic analyses were based on 124 genes derived from the single-cell transcriptomes of the microthoracid Pseudomicrothorax dubius and the nassulid Furgasonia blochmanni. The nassulid Nassula sorex from the Culture Centre for Algae and Protozoa was also included, but this isolate was discovered to have been misidentified. We first redescribe, using light and scanning electron microscopical techniques, this "N. sorex" as a new species of Nassula, Nassula variabilis n. sp., characterized by its highly variable nassulid frange. We have sequenced the single-cell transcriptomes to obtain data for phylogenomic analyses. These gave robust support for the Nassophorea, which are sister to a clade of Colpodea species. If our topology truly represents the order of divergence of taxa, a cytopharyngeal basket with microtubular nematodesmata and with Y and Z microtubular ribbons was likely an ancestral feature, at least of the Phyllopharyngea, Colpodea, Nassophorea, and Oligohymenophorea.
Keywords: Parahymenostomata; phylogeny; Phylogeny; Tetrahymena.; nasse; geny rRNA; Genes, rRNA; Tetrahymena; fylogeneze; Ciliophora; Paramecium